DOI: 10.11606/t.5.2020.tde-09012020-163231
|View full text |Cite
|
Sign up to set email alerts
|

Autocoleta cervicovaginal no rastreamento do câncer do colo do útero: aceitabilidade, detecção de Papilomavírus Humano de alto risco oncogênico e pesquisa de biomarcadores

Abstract: Sou feita de retalhos. Pedacinhos coloridos de cada vida que passa pela minha e que vou costurando na alma. Nem sempre bonitos, nem sempre felizes, mas que me acrescentam e me fazem ser quem eu sou. Em cada encontro em cada contato vou ficando maior... Em cada retalho, uma vida, uma lição, um carinho, uma saudade... Que me tornam mais pessoa, mais humana, mais completa. E penso que é assim mesmo que a vida se faz: de pedaços de outras gentes que vão se tornando parte da gente também. E a melhor parte é que nun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 95 publications
0
2
0
1
Order By: Relevance
“…Reasons for preferring self-sampling included being more practical, being able to collect samples at home, and feeling less shame and discomfort. 19 Women who undergo self-sampling are more likely to complete screening and follow-up colposcopy. 39 Ethical Implications of Increased Cervical Cancer Screening for Populations from Hhigher Social Classes Over-screening is common among Brazilians of higher social class, as demonstrated by 93.8% of study participants who think cytology should be done at greater frequency than recommended.…”
Section: Practicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Reasons for preferring self-sampling included being more practical, being able to collect samples at home, and feeling less shame and discomfort. 19 Women who undergo self-sampling are more likely to complete screening and follow-up colposcopy. 39 Ethical Implications of Increased Cervical Cancer Screening for Populations from Hhigher Social Classes Over-screening is common among Brazilians of higher social class, as demonstrated by 93.8% of study participants who think cytology should be done at greater frequency than recommended.…”
Section: Practicesmentioning
confidence: 99%
“…18 Studies have demonstrated the reliability of self-sampling vs clinician-sampling in Brazilian contexts and revealed high acceptability of self-sampling. 19 However, widespread HPV testing has low specificity, which can increase colposcopy referrals by 4-fold. 16 Traditional colposcopy allows for the diagnostic confirmation of abnormal cells in the cervix, but is not widely available, and is invasive, causing pain and discomfort.…”
Section: Introductionmentioning
confidence: 99%
“…Para tanto, alguns tipos são considerados de elevado risco e infectam também outros tipos celulares como as células do ânus, vagina, pênis, boca, língua entre outros. (Lorenzi et al, 2019).…”
Section: Introductionunclassified